Surgically assisted medical management of interstitial ectopic pregnancy - Devi, Lekshminarayanan Thulasi; Kumar, Sangeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
An interesting case of interstitial ectopic pregnancy in a primigravida managed by surgically assisted medical management with intracardiac instillation of KCl and methotrexate. It was diagnosed based on transvaginal and transabdominal ultrasound and procedure was done as USG guided under local anaesthesia in OPD by transabdominal route and immediate disappearance of foetal cardiac activity was noted on Doppler. She was followed up with serial sβ-hCG and TVS. She had no post procedure complication and was discharged on day 2 of procedure.